2015
DOI: 10.1039/c4an01832j
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of a lung cancer spectral histopathology (SHP) data set

Abstract: We report results on a statistical analysis of an infrared spectral dataset comprising a total of 388 lung biopsies from 374 patients. The method of correlating classical and spectral results and analyzing the resulting data has been referred to as spectral histopathology (SHP) in the past. Here, we show that standard bio-statistical procedures, such as strict separation of training and blinded test sets, result in a balanced accuracy of better than 95% for the distinction of normal, necrotic and cancerous tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 30 publications
1
46
0
1
Order By: Relevance
“…The CIs were also obtained by analytical methods and agree very well with the simulations. 12 The results of this simulation also suggest that the annotation method described earlier that often yields hundreds or thousands of individual pixel spectra for each annotated spot produces a representative sampling of tissue homogeneity and patient-to-patient variance. This is in contrast to other cancer diagnostic methods that yield one data point per patient, whereas in SHP thousands of data points are created for each patient.…”
Section: Computational Aspectsmentioning
confidence: 88%
See 3 more Smart Citations
“…The CIs were also obtained by analytical methods and agree very well with the simulations. 12 The results of this simulation also suggest that the annotation method described earlier that often yields hundreds or thousands of individual pixel spectra for each annotated spot produces a representative sampling of tissue homogeneity and patient-to-patient variance. This is in contrast to other cancer diagnostic methods that yield one data point per patient, whereas in SHP thousands of data points are created for each patient.…”
Section: Computational Aspectsmentioning
confidence: 88%
“…12 In the work described therein, efforts were reported that detailed the composition, in terms of patients and pixel spectra, of the training and validation data sets, the metrics used for the evaluation of the quality of the diagnostic results, the type of MLAs, the number of pixels per patient to be included in the training phase, the number of spectral features (data points per spectrum) included in the analysis, and a measure of the power and confidence interval of the classification. This Table 2 Number of pixel spectra, processed spectra, and annotated spectra in entire TMA data set Total spectra:…”
Section: Computational Aspectsmentioning
confidence: 97%
See 2 more Smart Citations
“…Using appropriate machine learning techniques, the sample can be classified into distinct groups. This has extensively been done on lung tissue samples [2,5,20], down to the sub-classification of adenocarcinoma subtypes [9].…”
Section: Introductionmentioning
confidence: 99%